(untitled) (LEGAL DIALOGICA, 2025)
Zarda Alfia Hani 04020210053 Supervised by Hambali Thalib as the Principal Supervisor and Sutiawati as the Co-Supervisor. This research aims to analyze the regulation of criminal offenses punishable by the death penalty and compare the formulation of the death penalty between the Penal Code under Law Number 1 of 1946 (Dutch Colonial Penal Code) and Law Number 1 of 2023 concerning the Penal Code (National Penal Code). This study employs a normative legal research method with a statutory approach and a case approach. Legal data were collected through literature studies and analyzed qualitatively. The findings of this research indicate that the regulation of criminal offenses punishable by the death penalty in Indonesia is found in the Penal Code, the Narcotics Law, the Human Rights Law, the Corruption Crime Law, the Human Rights Court Law, and the Law on the Misuse of Firearms and Explosives. Furthermore, a comparison of the death penalty between the Dutch Colonial Penal Code and the National Penal Code of 2023 reveals a shift from the death penalty as a principal punishment to a death sentence with a probationary period and an alternative life imprisonment sentence. The comparison also includes differences in the legal basis, the formulation of the death penalty, the criteria for its application, and the procedures for its execution. This research recommends further studies on severe crimes that have not been explicitly regulated for the application of the death penalty. Abstrak: Zarda Alfia Hani. 04020210053. Analisis Yuridis Perbandingan terhadap Hukum Pidana Mati dalam Undang-Undang Nomor 1 Tahun 1946 dengan Undang-Undang Nomor 1 Tahun 2023. Dibawah Bimbingan Hambali Thalib sebagai Ketua Pembimbing dan Sutiawati sebagai Anggota Pembimbing. Penelitian ini bertujuan unutk menganalisis pengaturan tindak pidana yang diancam pidana mati serta perbandingan pengaturan rumusan pidana mati antara Kitab Undang-Undang Hukum Pidana Nomor 1 Tahun 1946 (KUHP Kolonial Belanda) dengan Undang-Undang No.1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana (KUHP Nasional) Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan kasus. Data hukum dikumpulkan melalui studi literatur dan dianalisis secara kualitatif. Hasil penelitian ini menunjukkan bahwa Pengaturan Tindak Pidana yang diancam dengan Pidana Mati berdasarkan hukum di Indonesia dapat dilihat pada KUHP, Undang-Undang Narkotika, Undang-Undang Hak Asasi Manusia, Undang-Undang Tindak Pidana Korupsi, Undang-Undang Pengadilan HAM dan Undang-Undang Penyalahgunaan Senjata Api dan Bahan Peledak. Serta, Perbandingan Pidana Mati dalam KUHP Kolonial Belanda dan KUHP Nasional 2023 menunjukkan pergeseran dari pidana pokok menjadi pidana mati dengan masa percobaan dan alternatif hukuman penjara seumur hidup, perbandingan dalam dasar hukum, rumusan pidana mati, kriteria penerapan pidana mati serta prosedur pelaksanaan pidana mati Penelitian ini merekomendasikan pengkajian lebih lanjut terhadap jenis kejahatan berat yang belum secara eksplisit diatur untuk dikenakan pidana mati. Kata Kunci: Perbandingan, Pidana Mati, Tindak Pidana, KUHP.